Influência do anel de contenção na evolução pós-operatória dos pacientessubmetidos à gastroplastia vertical em "Y de roux para tratamento da obesidade mórbida - Silvia Zenobio Nascimento (2012)
Introduction: Morbid obesity (MO), and correlated diseases has become a serious problem for public health. The surgical treatment of MO is considered the most efficient method of sustained weight loss. Roux-en-Y gastric bypass procedure (RYGBP) is one of the most commonly performed procedure in Brazil and worldwide. The use of a restrictive ring can be added to this procedure to slow the rate of emptying from the gastric pouch, causes satiety and reduces the calories intake. The restrictive ring can avoid the dilation of the gastric pouch and promote significant and long-lasting weight loss. The enlargement of the gastric pounch or gastric outlet has also been related to the re-gaining of weight. Aim: To evaluate the results in the first year after performing bariatric surgery, the weight loss, post-operative complications, and the impact of the surgery on diseases associated with MO and the quality of life of the individuals submitted to RYGBP, both with and without the restrictive ring. Method: This work is a comparative and retrospective study in which 68 patients who underwent surgery for MO were evaluated and divided into two groups: group 1 consisting of 36 patients who were submitted to RYGBP with the silastic ring and group 2 consisting of 32 patients submitted to the RYGBP without the restrictive ring. Data was collected by means of a BAROS questionnaire. This work was authorized by the Research Ethics Committee from Universidade Federal de Minas Gerais (UFMG), and all participants signed a free consent form. This study also sought to compare the weight losses, the percentage of excess in the loss of body mass index (%ELBMI), and the body mass index (BMI) after 12 months of post operative follow-up. The groups were also compared regarding the amount of impact on the co-morbidities related to MO and the complications arising from post-operative follow-up. Statistical analyses were performed using the Chi-squared test, the Students t testand the Z test and values were considered significant when p<0.05. Results: After 12 months, the BMI presented no significant difference between the groups (p=0.346). However, the %ELBMI in group 1 proved to be higher (p=0.032) when compared to group 2. The impact on the diseases associated with MO was similar between the groups, except for systemic arterial hypertension, which showed better results in group 2 (p=0.010). The most common complications in group 1 included depression (50%), anemia (41.7%), vomiting (61.1%) and incisional hernia (33.3%). In group 2, the most common complications included incisional hernia (25%), anemia (21.9%), vomiting (18.8%) and skin infections (15.6%). Group 1, as compared to group 2, showed a higher frequency of vomiting (p=0.010), depression (p=0.045), and anemia (p=0.019). Three patients (8.3%) presented a movement of the restrictive ring, given that in two (5.5%) it was necessary to remove it by laparotomy due to the symptoms of vomiting and diet intolerance. Nevertheless, this removal occurred after the second year of post-operative follow-up. Conclusion: The use of the restrictive ring favors a more significant weight loss when associated with RYGBP. However, the patients with the restrictive ring presented a higher frequency of vomiting, which may well indicate a negative impact on ones food tolerance and quality of life. The choice for this surgical technique must consider the advantages and disadvantages of each factor in an attempt to improve results and satisfaction among patients.